Teaching module that integrates visualization tools and inquiry to adress the concepts of reversibility, incomplete conversion and dynamic equilibrium - Özdemir, İlkay Buket Ataç. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
This study aimed to develop and measure the effectiveness of an instructional module ChemEq to help students conceptualize incomplete conversion, reversibility and dynamic equilibrium concepts of chemical equilibrium. In ChemEq instructional module inquiry based lab activity, animated display and lecture were integrated to relate macroscopic, submicroscopic and symbolic levels. In order to analyze the effectiveness of ChemEq instructional module, a pre-experimental design (pre-test post test design) was implemented in an Anatolian high school in Istanbul with the participation of 39 (Grade 11) students. Learning gains were determined by comparing students who differed in terms of their performance during the activities (lab activity and animated display activity) and chemistry achievement. Data obtained from the sample were analyzed to examine the impact of ChemEq instructional module on students’ conceptual understanding of the basic concepts as reversibility, incomplete conversion and dynamic nature of chemical equilibrium. Independent samples t-test and repeated measures ANCOVA was used for analysis of data. Results indicated that students’ molecular representation of the equilibrium state were not significantly different for groups who differed in terms of their performance during the lab activity and chemistry grades. Post animation measures also indicated that molecular representation of equilibrium state was not significantly different for groups who differed in terms of performance during the animated display activity. Repeated measures of ANCOVA showed significant difference between performance during the animated display and students’ understanding of the dynamic nature of the equilibrium state. Independent samples t-test and ANCOVA measures indicated no significant difference in retention scores (midterm grades) of student groups who differ in terms of their activity scores (lab activity and animated display activity). When the contribution of the both activities on the performance of a transfer measure about different but a related topic (weak acid and base equilibrium) was examined, results indicated a significant difference between activity total scores and transfer scores. Results implied that the animated display helped students to visualize the reactions taking place at submicroscopic level. Also transfer results implied that the difference in transfer scores of high and low performing groups of both activities were due to activity involvement rather than their chemistry achievements.
Keywords: Chemistry -- Study and teaching.; Chemical equilibrium.